DEVELOPING INFORMATION AND TECHNOLOGICAL COMPETENCE OF PROSPECTIVE MILITARY SAILORS - Ruslan Shevchenko; Oleh Cherniavskyi; Vasyl Shemchuk; Olena Zlobina; Natalia Benkovska; Nataliia Terentieva; Андрій Гуралюк (Інформаційні технології і засоби навчання)
The readiness of future officers of the Naval Forces of Ukraine to protect the Motherland, to perform official duties in units and on ships, requires them to receive a high level of professional training. An essential aspect of this training is the development of information and technological competence. Modern requirements, including the transition to material and technical standards aligned with NATO, necessitate an elevation in the level of information and technological competence among cadets.